Identification of CDK2-Related Immune Forecast Model and ceRNA in Lung Adenocarcinoma, a Pan-Cancer Analysis - Liu, Ting-Ting; Li, Rui; Huo, Chen; Li, Jian-Ping; Yao, Jie; Ji, Xiu-li; Qu, Yi-Qing (Frontiers in Cell and Developmental Biology, 2021)
Background: Tumor microenvironment (TME) plays important roles in different cancers. Our study aimed to identify molecules with significant prognostic values and construct a relevant Nomogram, immune model, competing endogenous RNA (ceRNA) in lung adenocarcinoma (LUAD). Methods: “GEO2R”, “limma” R packages were used to identify all differentially expressed mRNAs from Gene Expression Omnibus (GEO) and The Cancer Genome Atlas (TCGA) databases. The function analysis of 250 overlapping mRNAs was shown by DAVID and Metascape softwares. By UALCAN, Oncomine and R packages, we explored the expression levels, survival analyses of CDK2 in 33 cancers. “Survival”, “survminer”, “rms” R packages were used to construct a nomogram model of age, gender, stage, T, M, N. Univariate, and multivariate Cox regression were used to establish prognosis-related immune forecast model in LUAD. Results: A total of 250 differentially expressed genes (DEG) were identified to participate in many cancer-related pathways, such as activation of immune response, cell adhesion, migration, P13K-AKT signaling pathway. The target molecule CDK2 had prognostic value for the survival of patients in LUAD (P=5.8e-15). Through Oncomine, TIMER, UALCAN, PrognoScan databases, the expression level of CDK2 in LUAD was higher than normal tissues.Through TISIDB database, we selected 13 immunodepressants, 21 immunostimulants associated with CDK2 and explored 48 genes related to these 34 immunomodulators in cBioProtal database (P<0.05). Gene Set Enrichment Analysis (GSEA) and Metascape indicated that 49 mRNAs were involved in PUJANA ATM PCC NETWORK (ES=0.557, P=0, FDR=0), SIGNAL TRANSDUCTION (ES=-0.459, P=0, FDR=0), immune system process, cell proliferation. Forest map and Nomogram model showed the prognosis of patients with LUAD (Log-Rank=1.399e-08, Concordance Index=0.7). Cox regression showed that four mRNAs (SIT1, SNAI3, ASB2, CDK2) were used to construct the forecast model to predict the prognosis of patients(P<0.05). LUAD patients were divided into two different risk groups (low and high) had a statistical significance (P=6.223e-04). By “survival ROC” R package, the total risk score of this prognostic model was AUC= 0.729 (SIT1=0.484, SNAI3=0.485, ASB2=0.267, CDK2=0.579). Conclusions: In conclusion, our study identified CDK2 related immune forecast model, nomogram model, forest map, ceRNA network, IC50 of anti-tumor drugs.